2023
DOI: 10.1021/acs.biomac.2c01526
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotides as Inhibitors of Ice Recrystallization

Abstract: Oligonucleotides of adenine (A20), guanine (G20), cytosine (C20), thymine (T20), cytosine–guanine ((CG)20), and adenine–thymine ((AT)20) were investigated as model compounds for ice recrystallization inhibition (IRI). Dehydroxy uracil (dU20), U20, and T20 were also compared to investigate the effect of minute changes in the hydrophobicity of the oligonucleotides on the IRI activity. Among the oligonucleotides considered in this study, T20 exhibited the best performance for IRI. In addition, the degree of polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…When PATs-2 and PATs-4 were compared, which have a similar the degree of succinylation but differ in l -Ala content, β-sheet content, IRI, INI, and TH activities increased as the L- Ala content increased. In particular, PATs-3 and PATs-4 with a high l -Ala content exhibited moderately high IRI activity with 30–35% of MLGS to that of PBS, which is similar to that of oligothymine (T20), facially amphiphilic copolymers of poly­(fulvo- co -oxo), nylon-3 copolymers. High DIS activities of PATs-2, PATs-3, and PATs-4 suggest that succinate groups as well as the l -Ala content play a role in the binding of PATs to the ice crystal surface. In particular, the LDH stabilization activity during freeze–thaw cycles was excellent for PATs-2, PATs-3, and PATs-4.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When PATs-2 and PATs-4 were compared, which have a similar the degree of succinylation but differ in l -Ala content, β-sheet content, IRI, INI, and TH activities increased as the L- Ala content increased. In particular, PATs-3 and PATs-4 with a high l -Ala content exhibited moderately high IRI activity with 30–35% of MLGS to that of PBS, which is similar to that of oligothymine (T20), facially amphiphilic copolymers of poly­(fulvo- co -oxo), nylon-3 copolymers. High DIS activities of PATs-2, PATs-3, and PATs-4 suggest that succinate groups as well as the l -Ala content play a role in the binding of PATs to the ice crystal surface. In particular, the LDH stabilization activity during freeze–thaw cycles was excellent for PATs-2, PATs-3, and PATs-4.…”
Section: Discussionmentioning
confidence: 75%
“…Both PATs-3 and PATs-4 showing rather high IRI activity have a similar 68–69% of l -Ala content. The control of hydrophobicity must be an important factor in designing a polymer with a high IRI activity as reported in PEG–poly­( l -Ala) block copolymers, oligothymines, and facially amphiphilic copolymers. ,, Based on the MLGS analysis, PATs-3 and PATs-4 have moderately high IRI activity compared to oligothymine (T20), facially amphiphilic copolymers of poly­(fulvo- co -oxo), nylon-3 copolymers with the 50:50 composition of a dimethyl methylammonium/monohydroxy methyl group. Molecular weight affects the IRI activity. ,,, The IRI activity of PVA is low for polymers with molecular weights less than 2 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Some dynamic ice-shaping studies showed that methyl-mediated IRI materials do not bind to the ice surfaces. , Therefore, unlike antifreeze materials having OH groups, MeMP-AgNP and MeOMP-AgNP do not interact with any facets of ice crystals through hydrogen bonding. It has been indicated that the Raman band of methyl groups shows a blue shift when they interact directly with water through hydrogen bonds. , However, as discussed above, upon freezing, the Raman band of methyl groups showed red shifts in some cases and blue shifts in others.…”
Section: Resultsmentioning
confidence: 99%
“…Freezing is commonly used in biopharmaceutical manufacturing and the storage of foods, tissues, and cells, but ice recrystallization can damage these substances during cryopreservation. Ice recrystallization causes mechanical damage and osmotic shock, which can decrease cell recovery, reduce cell viability, and impair cell function. During the recrystallization process, larger ice crystals grow at the expense of smaller ones, known as Ostwald ripening.…”
Section: Introductionmentioning
confidence: 99%
“…The scaled-up production of AFPs with a reasonable cost is still difficult. Synthetic polymers have been widely developed as AFP biomimetics, such as poly(vinyl alcohol) (PVA), poly(ethylene glycol) (PEG), and their block copolymers. , Besides, pronounced IRI activities have also been seen on graphene oxide (GO), nanocelluloses with amphiphilic structures, and facially amphipathic glycopolymers synthesized by ring-opening metathesis polymerization, analogous to natural antifreezing glycoprotein such as poly([( l -Ala) x - co -( l -Thr succinate) y , nanogels, high molecular weight polyproline, oligonucleotides, and surface-functionalized MOF particles . Since synthetic materials are less active than natural AFPs, researchers are turning their focus to the higher-ordered nanostructures .…”
mentioning
confidence: 99%